A afectividade e sexualidade dos adolescentes com T21 que frequentam o 2.º e 3.º Ciclo do Ensino Básico público da área da Grande Lisboa e as suas implicações na transição para a vida adulta - Freire, Sofia (2016)
This is a qualitative research that emerges within a contradictory political context. Indeed, on the one hand, inclusive education is a general social and educational aim, but on the other hand, several barriers still make it difficult for students with trisomy 21 (T21) to have a quality education, namely empowering sexual education. Besides, scientific literature points that family and school affects how these students will experience their own affectivity and sexuality and, eventually, their transition to adulthood. In a period where equal opportunities for all, and social justice and equity are principles most valued, it is extremely important to understand the affectivity and sexuality of adolescents with trisomy 21 (T21) and its implications for adult life. Considering this, the two general objectives of the present study were: 1) To understand the affectivity and sexuality of adolescents with T21and their implications for the transition to adulthood and, 2) to develop a sex education program targeted at young teenagers with T21. Specific objectives were: a) to describe the emotional and sexual behaviors of young adolescents with T21, b) to understand / identify the attitudes of close relatives, teachers, teacher of special education and assistant of special education in what concerns the emotional and sexual behaviors of young adolescents with T21 and c) in what concerns their transition to adulthood. Participated in this study: four students with T21; their parents; their teachers/directors of the class; their special education teacher and their special education assistant. Data collection methods were the interview, participant observation and document analysis. Results highlight that, students with T21 exhibit affective-sexual behaviors; they want to form a family and to have a profession. The attitudes of parents and school constitute a controlling and repressing factor of the affective-sexual demonstrations of those students.